Art & Soul - M’Liss Runyon; Robin Havenick; J.D. Mackenzie; Victoria L. Davis; Jane White (2024)
Art & Soul started with the exchange of art between two friends - abstract paintings done in response to short poems. Sometimes the reverse would occur - the creation of an abstract watercolor or photograph prompted a new poem. This collaboration is known as ekphrasis, a very special partnership between the writer and artist. The process, which began so slowly, sped forward into a gentle, magical expression of love and trust among five creatives, all former community college colleagues. Art & Soul illustrates an intersection of words and images and a love for the ways in which art changes our lives.